Relative performance information, advice‐seeking, and trust in the manager - Cheng, Ta‐Tung (Stephanie) (Contemporary Accounting Research, 2025)
In this paper, I conduct three experiments to investigate whether and how relative performance information (RPI) influences employee advice‐seeking and how advice‐seeking, in turn, affects employees' trust in their manager. The first experiment shows that, in a setting where the manager can provide useful advice, RPI increases advice‐seeking frequency, which is marginally positively associated with trust in the manager. The second experiment indicates that RPI increases advice‐seeking frequency when the manager's advice is highly useful, with a marginally significant effect when the advice is of low usefulness. Mediation analyses reveal that RPI alleviates employees' concerns about self‐presentation toward their manager, thereby increasing advice‐seeking frequency, but only when the manager's advice is of high usefulness. The third experiment shows that advice usefulness impacts employees' trust in their manager by influencing their perceptions of managerial competence and benevolence. This paper discusses theoretical and practical implications of these findings.